Revitalizing Khilafah fi al-Ard for Sustainable Agriculture: An Ethical-Operational Framework from Quranic Exegesis - Afifi, Faisal; Heriyanto, Heriyanto (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2025)
Environmental degradation and the stagnation of farmer welfare in rural Indonesia demand a reorientation of the agricultural management paradigm toward one that is not merely technocratic but also ethical-spiritual. This study examines the concept of Khilāfah fī al-Arḍ as an ontological and axiological foundation for sustainable agricultural development through a thematic exegetical study of QS. Al-Baqarah: 30 and QS. Al-An‘ām: 141. Unlike previous studies that predominantly focus on normative environmental ethics, this research specifically synthesizes exegetical analysis into an ethical-operational framework for agronomy. Employing a qualitative-analytical method, this research integrates classical and contemporary exegetical traditions with an analysis of agronomic and socio-economic data regarding the national agrarian crisis of 2024. The findings demonstrate that QS. Al-Baqarah: 30 defines Khilāfah not as exploitative domination but as a mandate of Imārat al-Arḍ (earth stewardship) which requires competence in knowledge (‘ilm) and the prevention of ecological corruption (fasād). Meanwhile, QS. Al-An‘ām: 141 provides guiding principles for agricultural management through biological diversification (polyculture), distributive justice (ḥaqqahu), and input efficiency (lā tusrifū). The synthesis of these two verses generates an “Agricultural Ecotheology” paradigm that positions the farmer as a guardian of ecosystem balance (mīzān) and an agent of social justice. This framework is highly relevant for addressing soil fatigue caused by excessive agrochemicals and structural poverty in rural areas.